Construction of compressible dual thermally conductive boron nitride network supported by Polyurethane@Polydopamine skeleton for improved thermal management performance. (October 2022) - Li, Xin; Yang, Lei; Chen, Xiaolong; Jiang, Fang
Graphical abstract: Abstract: Due to the increasing heat dissipation problem of modern electronic components, polymer-based thermally conductive composites have attracted extensive attention. Whereas, the improvement of thermal conductivity of composites are often accompanied by the loss of mechanical properties. Here, we report the preparation of polymer-based thermally conductive composites containing dual thermally conductive networks consisting of macro and micro-networks by a simple aqueous dip-coating process combined with a layer-by-layer assembly of core–shell structures. The thermal conductivity of polyurethane@polydopamine@boron nitride/polydimethylsiloxane (FPB/PDMS) composite reaches 0.70 Wm −1 K −1 when the filling amount of boron nitride is only 3.80 vol%, the thermal conductive enhancement reaches 367 %, and toughness reaches 80.00 Jm −3, realizing the collaborative improvement of thermal conductive and mechanical properties. At the same time, the LED chip with the composite which serve as thermal interface materials (TIMs) can effectively dissipate heat, which exhibits thermal management application prospect.